PENERAPAN KONSELING KELOMPOK DENGAN TEKNIK TOKEN ECONOMI UNTUK MENGATASI PERILAKU BOLOS SISWA DI UPT SMAN 8 LUWU TIMUR (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This article is based on the author's observations and experiences, that in SMA Negeri 8 Luwu Timur there are still many students who skip school. The author's goal is to find out how to apply group counseling to overcome student truancy behavior in SMA Negeri 8 Luwu Timur. The conclusion of this research is that there are many students who like to skip school because of lack of motivation to learn, do not like certain subjects and lack of awareness of the importance of education. The author's efforts in overcoming the truancy behavior of Class XI students at SMA Negeri 8 Luwu Timur are: conducting group counseling using token economy techniques, namely the token economy is a behavior modification designed to increase unwanted behavior by using tokens (signs). . Individuals receive tokens immediately after displaying the desired behavior. The tokens are collected and can be exchanged for an object or full honor. In order to review the changes that exist in students, then (1) BK teachers are more involved in establishing communication between students; (2) BK teachers collaborate with related parties such as homeroom teachers and subject teachers.